VOCATIONAL TEACHERS’ OPINIONS ABOUT THE ALREADY ACQUIRED AND YET TO BE IMPROVED COMPETENCES IN THE CONTEXT OF THE FOURTH INDUSTRIAL REVOLUTION - Bankauskienė, Nijolė; Masaitytė, Ramunė; Ramanauskaitė, Alicija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The fourth industrial revolution is associated with the ever-increasing requirements for vocational training. The important factors that are required for the qualitative change of vocational training include increasing the diversity of the vocational training programs, optimization of the school network, increasing the effectiveness and interaction between primary vocational training and the training systems of the labor market, and effective improvement of the qualification/competences of vocational teachers. The understanding of the changing role of vocational teachers and the expression of their competences are directly related to the learning motivation, self-education, striving for continuous education, and orientation towards the improvement of the acquired professional qualification among the learners of vocational training centers. This paper presents theoretical insights into the vocational teachers’ competences, comparing the documents that regulate European and Lithuanian vocational training, and presents the results of the interview of a focus group with vocational teachers of Kaunas city vocational training centers. The qualitative study aimed at revealing which competences were expressed among vocational teachers in the context of the fourth industrial revolution. The study showed that the vocational teachers regarded the group of functional (activity) competences as most important for the quality of their work and recognized the influence of the fourth industrial revolution on changes in their competences.